2018
DOI: 10.1002/cpt.1078
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of Ceftriaxone and Metronidazole for Children With Severe Acute Malnutrition

Abstract: Infants and young children with severe acute malnutrition (SAM) are treated with empiric broad‐spectrum antimicrobials. Parenteral ceftriaxone is currently a second‐line agent for invasive infection. Oral metronidazole principally targets small intestinal bacterial overgrowth. Children with SAM may have altered drug absorption, distribution, metabolism, and elimination. Population pharmacokinetics of ceftriaxone and metronidazole were studied, with the aim of recommending optimal dosing. Eighty‐one patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…A recent study in Mozambique 22 noted dysentery to have an inverse association with death, and suggested that this could be linked to the treatment of dysentery with antibiotics. Antibiotic effectiveness among malnourished children might be decreased by delayed presentation to hospital, increased prevalence of antibiotic-resistant organisms, 23 or an altered pharmacokinetic profile, 24 which could explain the stronger association between dysentery and death in this group. Additionally, children with acute malnutrition are thought to be particularly vulnerable to dehydration, fluid overload, and electrolyte imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Mozambique 22 noted dysentery to have an inverse association with death, and suggested that this could be linked to the treatment of dysentery with antibiotics. Antibiotic effectiveness among malnourished children might be decreased by delayed presentation to hospital, increased prevalence of antibiotic-resistant organisms, 23 or an altered pharmacokinetic profile, 24 which could explain the stronger association between dysentery and death in this group. Additionally, children with acute malnutrition are thought to be particularly vulnerable to dehydration, fluid overload, and electrolyte imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative approaches, such as population PK (PopPK) and PBPK modeling and simulation, can be used to evaluate pediatric DDIs during drug development. PopPK modeling combined with sparse sampling is widely used to characterize drug disposition in neonates and children . Implementing allometric scaling for size in addition to a sigmoidal function accounting for organ maturation may be able to distinguish age and size effects on clearance from other patient‐specific factors, including DDIs .…”
Section: Opportunities For Evaluating Pediatric Ddismentioning
confidence: 99%
“…PopPK modeling combined with sparse sampling is widely used to characterize drug disposition in neonates and children. 7 Implementing allometric scaling for size in addition to a sigmoidal function accounting for organ maturation may be able to distinguish age and size effects on clearance from other patientspecific factors, including DDIs. 8 If a concomitant drug is identified as a significant predictor of variability in a PK parameter, simulations can be performed to optimize dosing for children receiving the drug combination.…”
Section: Opportunities For Evaluating Pediatric Ddis Modeling and Simmentioning
confidence: 99%
“…Other covariates such as comedications with vasopressor drugs or gentamicin, and pathology with severity score or edema are used in some specific studies (20,24,31,49).…”
Section: Discussionmentioning
confidence: 99%